Effects of Early Mobilization on Recovery Rate in Stroke Infarct Patients in Sobirin Lubuk Linggau Hospital - Dini Syavani; S. Effendi; Yuliawati Yuliawati (Jurnal Sains Kesehatan, 2018)
This study aimed to study the effect of early mobilization on recovery rates in stroke infarct patients in Sobirin Lubuk Linggau Hospital.The design used in this study was Pre Experimental using the one group pretest postest design. The population of this study were all infarction stroke patients at Sobirin Lubuk Linggau Hospital in July-August 2018. Sampling in this study used Accidental Sampling techniques of 24 patients. This study used primary data and secondary data. Primary data was data obtained through direct research using index brainstorm observation sheets in infarction stroke patients in Sobirin hospital. Secondary data in the form of books, literature, research journals, and internet studies related to research objects. The data obtained was then entered into the form. Data analysis was done by univariate, bivariate with Chi-Square Test.The results were obtained: (1) Of the 24 infarction stroke patients, the recovery rate before early mobilization was obtained with a minimum value of 1, a maximum of 11, an average of 4.62 with a standard deviation of 3.28; (2) Of the 24 infarction stroke patients, recovery rates after early mobilization were obtained with a minimum value of 1, a maximum of 13, an average of 6.04 with a standard deviation of 3.906; (3) There was an influence of early mobilization on recovery rates in stroke infarct patients in Sobirin Lubuk Linggau Hospital Keywords: early mobilization, infarct stroke, rate of recovery